2023
DOI: 10.3389/feduc.2023.1258980
|View full text |Cite
|
Sign up to set email alerts
|

Faculty perception of online education: considerations for the post-pandemic world

Vian Ahmed,
Chiraz Anane,
Ayman Alzaatreh
et al.

Abstract: In the post-COVID era, academic institutions adapted curricula, utilizing aspects of the online delivery in full or partially. Consequently, this research focuses on identifying the factors that influence faculty perceptions of effective online delivery in higher education and comparing them with students’ perceptions. The study involves semi-structured interviews with 15 faculty members at a renowned university to gain insights into their online teaching experiences during the pandemic. Additionally, 51 facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The pandemic itself highlighted the need to improve online teaching. Ahmed et al (2023) suggested that providing an effective learning environment requires effective communication, effective teaching strategies, effective technology integration, and faculty's willingness to adapt and improve teaching methods.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…The pandemic itself highlighted the need to improve online teaching. Ahmed et al (2023) suggested that providing an effective learning environment requires effective communication, effective teaching strategies, effective technology integration, and faculty's willingness to adapt and improve teaching methods.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%